(i) | \begin{equation} a < b \end{equation} |
(1) | \begin{equation} a = x_0 < x_1 < \cdots < x_N = b \end{equation} |
(2) | \begin{equation} \forall \, n \in \{ 1, \ldots, N \} : x_{n - 1} \leq x^*_n \leq x_n \end{equation} |
(i) | \begin{equation} a < b \end{equation} |
(1) | \begin{equation} a = x_0 < x_1 < \cdots < x_N = b \end{equation} |
(2) | \begin{equation} \forall \, n \in \{ 1, \ldots, N \} : x_{n - 1} \leq x^*_n \leq x_n \end{equation} |
(i) | \begin{equation} a < b \end{equation} |
(1) | \begin{equation} a = x_0 < x_1 < \cdots < x_N = b \end{equation} |
(2) | \begin{equation} \forall \, n \in \{ 1, \ldots, N \} : x^*_n \in [x_{n - 1}, x_n] \end{equation} |